Buletin Peternakan : PENGARUH PEMBERIAN BUNGKIL INTI KELAPA SAWIT YANG DIFERMENTASI MENGGUNAKAN ISOLAT SELULOLITIK DARI BELALANG KEMBARA PADA PAKAN TERHADAP PENAMPILAN PRODUKSI PUYUH JANTAN - Arif Pranata (Peternakan UGM, 2015)
This research was conducted to examine the effects of fresh and fermented palm kernel cake (BIKS)Ã‚ supplementation in the diets on male japanese quail performance. Two hundred and ten day-old quails were randomly devided into seven treatment diets in three replications of ten quails each. The dietary treatments were: diet without palm kernel cake (control; K), control diets supplemented with 10%, 20% , 30% BIKS (BIKS10%, BIKS20%, BIKS 30%), control diets supplemented with 10%, 20%, 30% fermented palm kernel cake (BIKSF10%, BIKSF20%, BIKSF30%).